Direct torque control technique for BLDC motor drive in electric vehicle applications - Chavhan, Sachin; Kumbhar, Mahesh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
In the field of electric vehicles (EV), the hunt for the appropriate choice of motor and its control technique would be a never-ending process. The brushless DC (BLDC) motors are deployed in electric vehicles on account of higher efficiency, long life, compact size, and higher torque capacity in comparison to other types of motors. The recent advancements in power electronics have assisted in the deployment of BLDC motors in electric vehicles. These applications demand a control mechanism for the motoring mode as well as the regenerative braking mode. During the motoring mode, the power delivered to the motor is controlled, and during the regenerative braking mode, the charging of the battery takes place. Speed control strategy during motoring mode is essential to guarantee the required performance. This paper presents a direct torque control (DTC) technique for BLDC motor control for electric vehicles. The control technique and drive setup are developed to cater to the motoring mode as well as regenerative braking operation as desired for electric vehicles. MATLAB simulation and results are discussed for both modes of operation. Also, the dynamic response of the system is analyzed, which shows an average 1.1 ms response time for a 100 RPM change in speed during speeding up and 0.76 ms response time while speeding down.